Peran Fintech (Aplikasi Stroberi Kasir) Dalam Meningkatkan Pengelolaan Keuangan UMKM di Kabupaten Belitung - Berandi Suaryansyah (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to assess the influence of the role of Fintech (Stroberi Cashier Application) in Improving SME Financial Management in Belitung Regency. The type of research used in this research is descriptive quantitative research. The total population is as many as 30 people. In this study, a sample of 30 people was used as a test sample for the instrument and a sample of research analysis data. Sampling in this study used the Sampling Saturated is sampling done as a whole from the total population. The processed data is the result of distributing questionnaires to SMEs in Belitung district. The data analysis technique used in this research is simple linear regression. Based on the results of data analysis, it can be concluded that the results of this study indicate the influence of path analysis of the financial technology model has a major influence on consumer satisfaction of 0.792 or 79.2%. It’s mean, financial technology has a significant influence on consumer satisfaction. Path analysis model II produces a direct effect of financial technology on the financial management of SMEs of -0.112 or 112% with a value of sig. 0.723 and the direct effect of consumer satisfaction on the financial management of SMEs is 0.037 or 3.7% with a sig. 0.907. It was concluded that financial technology